Analysis of Child Labor Rights Fulfillment Based on Maqashid Syariah - Marwa, Muhammad Habibi Miftakhul; Immawan Wahyudi; Fithriatus Shalihah (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Child Labor is a serious problem that has attracted national and international public attention. The purpose of writing this article is to analyze in depth the review of the fulfillment of child Labor rights based on maqashid sharia. This article's research method uses a type of normative legal research using secondary data obtained through literature study. The collected data was then analyzed descriptively qualitatively using a conceptual approach, namely the concept of maqashid sharia. The results and findings in this article are that Islam places the fulfillment of children's rights as an important thing to realize. The general aim of Allah SWT in sending down the Shari'a is to bring about benefits. The basic concept of benefit is realizing benefits and preventing harm. The practice of child Labor is prohibited, because it conflicts with the five main principles of maqashid sharia, namely the protection of religion, soul, mind, property and descendant, which are primary needs (dharuriyyah) that must be fulfilled in humans. The priority of a child's age is to fulfill the rights of religion, soul, reason and heredity rather than fulfilling the need for wealth.